2003
DOI: 10.1542/peds.112.4.890
|View full text |Cite
|
Sign up to set email alerts
|

Are Minority Children Under- or Overrepresented in Pediatric Research?

Abstract: Overall, we found an overrepresentation of black subjects and an underrepresentation of white and Hispanic subjects with significant variations depending on the type of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…23 Our work provides a different perspective, highlighting the central role of trust in the engagement of these communities. In support of this view, Wendler et al 3 found that when approached, minorities were no less likely to participate in research-and perhaps were even more receptive to participation.…”
Section: Discussionmentioning
confidence: 95%
“…23 Our work provides a different perspective, highlighting the central role of trust in the engagement of these communities. In support of this view, Wendler et al 3 found that when approached, minorities were no less likely to participate in research-and perhaps were even more receptive to participation.…”
Section: Discussionmentioning
confidence: 95%
“…In the past ten years, inclusion of ethnic and racial minorities in clinical trials has improved, but significant deficiencies remain in reporting the racial and ethnic make up of the population studied [4]. This was true in 40% of the pediatric studies cited by Walsh and Ross [5]. More recently, in 2011, Geller and colleagues published an analysis of clinical trials published in major medical journals; one-fifth of the studies did not report sample sizes by racial and ethnic groups, and 64% did not provide any analysis by racial or ethnic groups [6].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The findings suggested that child health research infrequently reports race and ethnicity and even less frequently reports socioeconomic status (SES). 6,7 The authors proposed that future research examine the extent of reporting of race/ethnicity and SES coding for specific disease states and determine whether there has been a change in reporting over time, with increased interest in health disparities. In this study, we examined the changes in reporting of race, ethnicity, and SES, in comparison with age and gender, in the past decade.…”
mentioning
confidence: 99%